Lineart 27 : art fair (Gent : Lineart vzw Gent, 2008)
Fabre, Jan ; Hörl, Ottmar ; Bogart, Bram ; Soulages, Pierre ; Thomson, Svend ; Albrecht, Hans ; De Pauw, Pascal ; Vermeersch, Pieter ; Gelper, Johan ; Denys, Ward ; Raveel, Roger ; Visic, Loreta ; Naveau, Nadia ; Balleux, Stephan ; Driessens & Verstappen ; Weta Digital ; van Pottelsberghe de la Potterie, Catherine ; Mahana Nassar, Victor ; Van Hulle, Jelle ; De Keyzer, Dirk ; Ricourt, Wim ; Comyn, Christine ; Walpoth, Bruno ; Slabbinck, Frank ; Bofill, Josep ; van Straaten, Frans ; Vyvey, Martin ; Jacubowitz, Hélène ; Jonckiere, Rogette ; Gartner ; Schelstraete, Georges ; Roos & Chris ; Vermeersch, José ; Alonzi, Robert ; Zeyen, Francine ; Gangolf, Serge ; Polles, Claudio ; Axell, Evelyne ; Haring, Keith ; Kirsone, Evija ; Zitmanis, otto ; Setowski, Tomasz ; Borowski, Stanislav ; Moré, Ekaterina ; Fuchs, Daniel & Geo ; Beck Lefebvre, Eugenia ; Slavinsky, Ivan ; Viene, Daniel ; Bolenz, Ulrike ; Tipoti, Alick ; Rockman Napaljarri, Peggy ; Pauwels, Olivier ; Lingier, Johan ; Simsa, Patricia ; Van den Abeele, Jacques ; Itach, Ilan ; Morcillo, Dolores ; Muylaert, Monique ; Danel, Françoise ; Bellefroid, Fred ; Cleymans, Leo ; Agnew, Rachel ; Rioni, Thengis ; Zurkan, Juri ; Ovsiyko, Valentina ; Schnittmann, Michail ; Vanmechelen, Koen ; Corneille, Joseph ; Peellaert, Guy ; Haesevoets, Mieke ; Blommaerts, François ; van Eyck, Peter ; Plomteux, Léopold ; Engelfriet, Alexandra ; Delacroix, Catalina ; Fortunato, Franco ; Pam ; Vogel, Patrick ; Thiry, Catherine ; Hazuka, Jacek ; Fogtt, Andrzej ; Bajsarowicz, Michal ; Borowski, Andrzej ; Marszalek, Waldemar J. ; Clinckx, Christine ; Geuz ; Lazovsky, Ana ; Schroeder, Diane ; Darmon, Jonathan ; Dedrie, Mark ; Lingl-Rebetez, Jürgen ; Kodde, Jonneke ; Henderickx, Philip ; Labath, Frans ; Gangolf, Serge ; etc.
Naar aanleiding van Lineart 27 van 2008-12-05 tot 2008-12-09
Engels, Nederlands, Frans
boek